SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN DAN ANTITUMOR 20 TUMBUHAN OBAT ASAL KABUPATEN MANOKWARI - Bimo Budi Santoso (Jurnal Natural, 2008)
Flavanoid, steroid, and terpenoid contents of 20 Manokwari medicinal plants were analyzed. The antioxidant activity, total phenolic contents and antitumor activity of 20 Manokwari medicinal plants were also evaluated. The result shows that 83% positif to flavanoid test, 59% positif to terpenoid test and only 25% positif steroid. Antioxidant activity and total phenolic contents evaluated using Ferric Thiocianate (FTC) and Folin-Ciocalteu methods respectively. Antioxidant activity and total phenolic contents of medicinal plants were extracted by the traditional method, boiling in water and also in 80% methanol. Twenty plants evaluated in both exstracts have significantly varies of antioxidant activities and phenolic contents, A significant and linier correlation coefficient between the antioxidant activity and the total phenolic content was found in both aqueous (R2= 0,77) and methanol (R2 = 0,85). Antitumor activity was tested using cell maurine P-388 and only 2 of medicinal plants are active to inhibit cell maurine P-388. Comparing extraction efficiency of the two methods, the methanol extracted phenolic compounds more efficiently, and antioxidant activity of the extract was higher